Erratum: Pengaruh Media Pembelajaran Dan Koordinasi Terhadap Ketepatan Forehand Top Spin Tenis Meja - Diki Syafwan Subagja; Nurlan Kusmaedi; Komarudin Komarudin (STKIP Muhammadiyah Kuningan, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.619 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article